The Inflation and the price changes of selected gold futures during the COVID-19 pandemic and the war in Ukraine, 2020–2023 - Czech, Maria; Puszer , Blandyna (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2024)
The study’s main objective is to determine the relationship between the level of inflation and changes in the prices of selected gold futures contracts during the health crisis and war in 2020–2023. The study hypothesizes that there is a strong linear correlation between rising inflation levels and increases in gold price levels. Quantitative research used dynamic analysis and multiple linear regression analysis to determine the direction of changes in selected inflation indicators and the prices of selected gold futures, as well as to evaluate the impact of inflation on these prices. The study found that inflation showed a strong upward trend in Poland, the Eurozone, Switzerland, and the US. The highest levels of inflation, as measured by the Consumer Price Index (CPI), between 2020 and 2023 were recorded in the USA and Poland, while in the Eurozone and Switzerland, CPI levels were much lower. The article shows that inflation growth is not only due to changes in food and energy prices but also to increases in the prices of other goods and services, as indicated by the rising levels of core inflation in the countries studied. Despite rising inflation, the prices of gold futures remained relatively stable, with the exception of Gold PLN Futures, which saw prices increase. The study demonstrates that inflation affects the prices of selected gold futures, but also that the impact of inflation on their prices is heterogeneous, varying both in terms of the direction and strength of the impact.